(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: Financial banking intermediaries are sensitive to changes in market interest rates. The volatility of market interest rates affects the level of bank net interest income and determines the bank interest rate policy. Banks are actively managing structural interest rate risks to mitigate the negative effects of changes in market interest rates. The post-crisis period is characterised by unconventional monetary policy, and one of the basic objectives of the monetary instrument is a negative interest rate policy. This paper researches the effects on the bank net interest income structure with an impact on bank performance indicators. The basic research hypothesis is that during the financial crisis and a negative interest rate policy, the movement of bank interest income does not converge compared to a bank interest expense. Methodology: According to the characteristics of the dataset, which includes 32 listed banks from Great Britain, Switzerland and the European Union for the period 2002-2019, panel data analysis is applied. To analyse the effect of the interest rate level on total interest income and total interest expense, we formed two models. Fixed-effects models were used for parameter estimation. Results: A bank interest expense is more sensitive to unconventional macroeconomic policy than bank interest income. Conclusion: The traditional interest earning customer related business can enable banks to stabilise the bank performance indicator during market disruption.